The Implementation of Community Development with Potentials Cultural, Fisheries and Culinary in Lance Village, Batam for Community Based Tourism and Economic Sustainability by PT Perusahaan Gas Negara (Sales and Operation Region I) - Indri Agstenesya; Tri Apriansyah; Suprayogi Suprayogi (International Journal of Economics, Business and Innovation Research, 2024)
Island communities around the world face complex challenges, mainly due to geography and limited resources. In Indonesia, these challenges are compounded by uneven development, resulting in limited access to basic services such as health and education. Batam Island, as a major industrial hub, reflects many of the problems common to other islands, including rapid urbanization, increased population density, and environmental issues. This research focuses on Lance Island around Batam, which has great potential in marine and tourism. The community empowerment program by PT Perusahaan Gas Negara (PGN) aims to improve the quality of life of the community through economic development, education, health, and the environment. This approach is in line with the principle of Community Based Tourism (CBT) which places the community as the main actor in tourism development. This research uses a qualitative method with purposive sampling technique to extract data from relevant informants. The results show that the community empowerment program has provided significant positive impacts, including economic improvement, women's empowerment, cultural preservation, and tourism development. Commitment to sustainability and strong cooperation between the company, educational institutions, and local communities are key to the success of this program.